2020
DOI: 10.1108/mf-09-2019-0457
|View full text |Cite
|
Sign up to set email alerts
|

Bank competition in India: revisiting the application of Panzar–Rosse model

Abstract: PurposeThe paper measures the degree of bank competition in Indian banking over the period 1996–2016. Using bank-level annual data, we revisit the case of banking competitiveness during the prefinancial and postfinancial crisis and examine whether the global financial crisis alters the level of bank competition in India. Additionally, this paper addresses the misspecification issues associated with the widely used Panzar–Rosse model in Indian banking context.Design/methodology/approachWe apply Panzar and Rosse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
3
6
2
Order By: Relevance
“…The first regressor LC revealed that a high labor cost paid by banks to their employees increases the bank's interest income. This result is harmonious to the prior empirical findings of Akthan and Mosood (2010); Biekpe (2011); Gajurel and Pradhan (2012); Neupane (2016); Fosu (2013); Simatele (2015); Apergis (2015); Sakar and Sensharma (2016); Barros and Mendes (2016); Tan (2016);Tihir et al (2016); and Rakshit and Bardhan (2020). This empirical evidence elucidated that a higher level of financial benefit increases employees' morale, dedication, and loyalty to the organization and increase the overall efficiency and productivity of the banks.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The first regressor LC revealed that a high labor cost paid by banks to their employees increases the bank's interest income. This result is harmonious to the prior empirical findings of Akthan and Mosood (2010); Biekpe (2011); Gajurel and Pradhan (2012); Neupane (2016); Fosu (2013); Simatele (2015); Apergis (2015); Sakar and Sensharma (2016); Barros and Mendes (2016); Tan (2016);Tihir et al (2016); and Rakshit and Bardhan (2020). This empirical evidence elucidated that a higher level of financial benefit increases employees' morale, dedication, and loyalty to the organization and increase the overall efficiency and productivity of the banks.…”
Section: Discussionsupporting
confidence: 88%
“…The long-run market equilibrium finding was matching to the outcomes obtained by Gajurel and Pradhan (2012) and Neupane (2016) for Nepalese banking. However, this result is incompatible with the study of Rakshit and Bardhan (2020) in the Indian context. Further "The market equilibrium test is conducted in order to draw inference on the impact of the explanatory variables on ROA" (Rakshit & Bardhan, 2020).…”
Section: Equilibrium Test Results and Sensitivity Analysiscontrasting
confidence: 57%
See 3 more Smart Citations